Asia's labour-driven economic development, flying-geese style: An unprecedented opportunity for the poor to rise? - Terutomo Ozawa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
The notion of `shared growth' was introduced by the World Bank in recognition of East Asia's rapid growth accompanied by poverty reduction. It emphasizes the criticality of pro-poor policies and institutional setups in the fast-developing East Asian economies. The efforts of these individual countries are, however, a necessary but not sufficient condition (explanation). There is a more essential, underlying region-wide mechanism that simultaneously promotes regionalized growth and specifically favours Asia's working mass of unskilled labour. Such an efficacious mechanism is posited in the `flying-geese paradigm of comparative advantage recycling in labour-intensive goods'. The paper argues that a number of favourable factors have fortuitously coalesced to engender a considerably favourable condition for Asia's rapid catch-up growth in which unskilled labour (the poor) can participate as their countries' most vital input in labour-driven development.
Keywords: F20; F23; F43; J31; L6; O14; 330; flying-geese theory; trade; growth; poverty reduction; comparative advantage; recycling; labour-driven economic development; Wirtschaftswachstum; Asien; Flying Geese Muster